Applying Imam Al-Mawardi’s Views on the Hisbah system in Islam - Habibullah, Muhammad Dhiya'ul Haq; Alwi, Muhammad Chafidz (Syariah: Journal of Fiqh Studies, 2024)
This study aims to identify Imam Al-Mawardi’s views on the Hisbah system in Islam and practice (andi the ‎practice) of the system. Imam Al-Mawardi was one of the first scholars to speak in his work about the ‎importance of Hisbah thought in Islam. As for the method used to achieve the objectives of this research, it ‎is the method of analysis based on the content, which is based on the method of qualitative research, and ‎the analysis is based on his ideas about the Hisbah, from his books, Al-Ahkam Al-Sultaniyyah, Al-Rutbah fi ‎Thalab Al-Hisbah, Adab Al-Dunya wa Ad-Din, and other things. Based on the results of this research, it ‎ is clear that Hisbah, according to Imam Al-Mawardi, is divided into two parts: the ‎authority to call for good (enjoin what is right) and prevent evil (forbid what is evil). These two sections are ‎divided into three important elements, which are related to the pure and pure rights of God, pure and ‎purely human rights, and the rights of those who are dual. Al-Mawardi believes that the ‎Hisbah has the authority to determine discretionary punishments for violators of Islamic law and violators ‎of the public interest, but it is limited and does not have the authority to determine Hadd punishments. The ‎course of this study attempts to provide a basic framework for hisbah from the point of view of Imam Al-‎Mawardi, which can be referred to in the application of hisbah today in government.